2013
DOI: 10.1021/jp403483q
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrophobic Micelle Structure on Crystallization of the Photosynthetic RC-LH1-PufX Complex from Rhodobacter blasticus

Abstract: Small angle X-ray scattering (SAXS) experiments are performed on two non-ionic surfactants, the dodecyl β-maltoside (DDβM) and the propyl(bi)cyclohexyl α-maltoside (PCCαM), a maltoside derivative containing a rigid bicyclohexyl group as hydrophobic chain, in order to compare the influence of both hydrophobic moiety structure and anomeric form on micelle form factors and intermicellar interactions relevant for membrane protein crystallization. Density and refractive index measurements were performed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
3
14
0
Order By: Relevance
“…We thus found that A 2 is +0.7 Â 10 À4 mol ml g À2 for F 2 H 9 --M and +0.08 Â 10 À4 mol ml g À2 for F 6 H 2 --M in water, with the decrease in the repulsive contribution of the second virial coefficient being owing to an increase in the micelle size (Tanford, 1961). The change observed in D t for F 2 H 9 --M and F 6 H 2 --M can therefore be attributed to interactions between micelles, as was observed for DD--M (Barret et al, 2013). The decrease in D t of F 4 H 5 --M may, in contrast, be correlated to the increase in micelle size.…”
Section: Data From Saxsmentioning
confidence: 58%
See 1 more Smart Citation
“…We thus found that A 2 is +0.7 Â 10 À4 mol ml g À2 for F 2 H 9 --M and +0.08 Â 10 À4 mol ml g À2 for F 6 H 2 --M in water, with the decrease in the repulsive contribution of the second virial coefficient being owing to an increase in the micelle size (Tanford, 1961). The change observed in D t for F 2 H 9 --M and F 6 H 2 --M can therefore be attributed to interactions between micelles, as was observed for DD--M (Barret et al, 2013). The decrease in D t of F 4 H 5 --M may, in contrast, be correlated to the increase in micelle size.…”
Section: Data From Saxsmentioning
confidence: 58%
“…In this context, we characterized the assembly properties of a new rigid surfactant, trans-propyl(bi)cyclohexyl--maltoside (PCC--M; Glycon), which was synthesized and described for MP stabilization and crystallization (Hovers et al, 2011). In terms of the shape and size of the micelles, we showed that whereas DD--M and PCC--M present quite similar ellip-soidal shapes and sizes, the aggregation number (N agg ) is larger for PCC--M (N agg ' 165) than for DD--M (N agg ' 125) (Barret et al, 2013). Moreover, the study of intermicellar interactions via measurement of the second virial coefficient (A 2 ) for rational crystallization showed PCC--M to be more attractive than DD--M, inducing a lower cloud-point boundary for PCC--M than for DD--M. Although the solubility of RC-LH1-pufX in this new surfactant was found to be lower and crystallization was found to be easier (Barret et al, 2013), the diffraction quality was not increased sufficiently to make structure resolution possible, which is most likely to be the result of the detergent 'belt' surrounding the protein being too large (which is related to the higher aggregation number of PCC--M), therefore causing steric interference in the crystalline lattice.…”
Section: Introductionmentioning
confidence: 87%
“…This parameter could therefore be exploited to rationally manipulate solution conditions in order to favor crystal growth. In the particular case of membrane proteins, several significant successes have been reported in which explicit virial coefficient measurements have driven crystal optimization (Gabrielsen et al, 2010;Barret et al, 2013). However, despite strong evidence of the predictive value of this parameter, the virial coefficient is not yet widely measured during crystallization efforts.…”
Section: Mechanistic Approaches To Crystallization Of Proteindetergenmentioning
confidence: 99%
“…The behavior of MP in further purification and characterization steps will depend on the mixed micelles containing lipid, protein, and detergent formed during the extraction process. Usually, the use of excessive amounts of detergents prevents MP crystallization or the high-resolution diffraction of the crystals obtained, and may even produce their inactivation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PL removal may lead to the loss of biological activity of MP. Likewise, PL modifies the compactness of the Protein-Detergent-Lipid complex and to change the shape and resolution of MP-crystals, favouring crystallization [6]. For these reasons, it is of great interest to identify PL structures associated to MP.…”
Section: Introductionmentioning
confidence: 99%